ANALISIS PENGARUH KOMPETENSI PEGAWAI PAJAK, KINERJA PEGAWAI PAJAK, DAN KUALITAS LAYANAN PEMBAYARAN PAJAK KENDARAAN BERMOTOR TERHADAP KEPUASAN WAJIB PAJAK DI KANTOR SAMSAT KABUPATEN MINAHASA TENGGARA - Potalangi, Vinda Vebianti; Alexander, Stanly W.; Rondonuwu, Sintje (Universitas Sam Ratulangi, 2017)
Â Â Taxpayer satisfaction is the feeling of pleasure that the taxpayer obtains after performing his obligations in paying taxes, then comparing expectations with the performance provided by the tax officials. Taxpayer satisfiction may be affected by the competence of tax employees, the performance of tax employees, and the quality of tax payment services in this case, namely motor vehicle tax. The purpose of this study is to determine the effect of the competency of the tax employee, the performance of the tax employee, and the quality of the motor vehicle tax payment service to the taxpayer satisfaction registered in the SAMSAT office of the Southeast Minahasa Regency.This type of research is quantitative research. The population in this study are all taxpayers who pay their motor vehiclle tax at the SAMSAT office of Southeast Minahasa Regency. The sample in this study amounted to 100 respondents. This study used multiple linier regression that the competence ofÂ employee tax (X1), employee performance tax (X2), and quality of motor vehicle tax payment service (X3) has an influence on taxpayer satisfactio.Keywords: Competence of Employee of Tax, Performance of Tax Officer, Quality of Tax Service of Motor Vehicle Tax and Taxpayer Satisfaction.